132k views
0 votes
Which expression below gives the average rate of change of the function g(x) = -x^2 - 4x on the interval 6 ≤ x ≤ 8 ?

Which expression below gives the average rate of change of the function g(x) = -x-example-1

2 Answers

4 votes

Answer:

A.

Explanation:

Δy /Δx = (y2 - y1)/(x2 - x1) = [g(x2) - g(x1)]/(x2 - x1)

[g(x2) - g(x1)]/(x2 - x1) =[g(8) - g(6)]/(8 - 6) =
([-8^(2)-4(8)]-[-6^(2)-4(6)])/(8-6)

User Pilkch
by
5.1k points
2 votes

Answer:

1st Option

Explanation:

Average rate of change formula:
(f(a) - f(b))/(a-b)

Simply plug in 8 as a and 6 as b.

User Nagendra Kakarla
by
4.8k points